Spaceships and Poetry: Enlivening the Lab as a Site of Feminist Critical Pedagogy - Rachel Douglas-Jones; Baki Cakici; Marisa Leavitt Cohn; Simy Kaur Gahoonia; Mace Ojala; Cæcilie Sloth Laursen (Engaging Science, Technology, and Society)
Whilst STS has long studied lab work, the past few years have also seen the introduction of labs as social formations for doing STS enquiry. But what kind of contributions to pedagogy, particularly in technical universities, can STS inspired university labs make? We respond to the need to more deeply understand how teaching may be practiced as a site of STS experimentation by describing the work of the ETHOS Lab, our critical feminist lab at the IT University of Copenhagen, as ‘enlivening’. Using three events from 2017–2020 as case studies, we identify both the use of space and shaping of time as integral to how we have sought to trouble knowledge production in our own environment, particularly by creating sites and situations where teaching and research cannot be separated. By showing how our Lab activities intervene in ways of knowing and doing within university hierarchies and cultures, we aim to contribute an analysis of the critical potential of STS lab work in technical environments, and recommendations from our situated evolving space of feminist praxis within an interdisciplinary IT University.